Compound high-quality criteria: a new vision to guide the development of drugs, current situation. Issue 4 (April 2016) - Mignani, Serge; Huber, Scot; Tomás, Helena; Rodrigues, João; Majoral, Jean-Pierre
Highlights: Guides improving attrition rate from hits to final medicines are analyzed. HTS and fragment-based drug discovery approaches are detailed. Exploration of the chemical space as sources of new drugs is discussed. New paradigms of hit and lead generation and optimization process are presented. Abstract : For several decades, the pharmaceutical industry has suffered due to major issues such as reductions of the number of FDA approved drugs and biologics. Several analyses have been highlighted that the 'druglikeness' is one of the strategies to improve succeed rates of screening such as, for instance, high-throughput screening (HTS), and then hits (as starting point), leads and clinical candidates. It is clear that the improvement of compound quality accelerates the drug discovery projects. The monitoring of several indices to avoid 'molecular obesity' (ADMET problems) of final drugs from good-quality 'low-fat' starting points represents today a powerful strategy of optimization process. The development of the new guides to find drugs highlighting attempts at improving the attrition rate from hits to final medicines by focusing on how to improve the druggability of hits, leads and drugs during the drug discovery process represents a key approach to design next better generation of medicines. Teaser: The key points emerging to evaluate the quality of hits. Leads and consequently drugs represent today a powerful strategy of optimization process to improve the attrition rate from hits to final medicines are provided in this original review.